Investigation of antibacterial and photocatalytic efficiency of green ZnO nanoparticles that synthesized with Celosia Cristata flower extract - Ustun Ozgur, Mahmure; Duygulu, Ozgur; Altikatoglu Yapaoz, Melda (Tubitak Scientific & Technological Research Council Turkey, 2022)
Increasing interest in green chemistry has led scientists to an environmentally friendly nanoparticle synthesis approach that has many advantages, such as simple, affordable and versatility for a wide range of commercial production. In this study, green synthesis of zinc oxide nanoparticles (ZnO NPs), which is widely researched in the field of nanotechnology, was performed under different conditions (volume ratio of CC flower extract to Zn(CH3COO)(2) solution, time, pH and temperature) using the aqueous extract of Amarant (Celosia cristata L., CC, cockscome) plant flowers. Produced ZnO NPs were characterized by UV-Vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), high-resolution transmission electron microscopy (HR-TEM) and scanning electron microscopy (SEM) analysis. The characteristic absorption peak seen at lambda(max): 364 nm in the UV-Vis absorption spectrum and the band seen at 381 cm(-1) in the FTIR spectrum indicate that ZnO NPs were synthesized. TEM image also confirmed the formation of nanoparticles. The average size of nanoparticles is approximately 22-27 nm and the shape of the ZnO NPs as nearly spherical. The effect of different calcination temperatures (100, 200, 300, 400, and 500 degrees C) on the size of ZnO NPs was investigated and it was observed that the particle size decreased as the calcination temperature increased. ZnO NPs were also used as photo catalyst for removal of basic yellow28 (BY28) and basic violet39 (BV39) dyestuffs which are used in textile industry and ecologically toxic. The decolorization efficiency was found 95%-100% and 62% respectively when the BV39 and BY28 dyestuffs were exposed to UV light for 160 min. Antibacterial activity of ZnO NPs produced with different amounts of CC flower extract and calcined at different temperatures (100, 200, 300, 400, and 500 degrees C) was investigated using modified disc diffusion method. Produced ZnO NPs displayed antibacterial activity against Staphylococcus aureus and Escherichia colt bacterial strains and were more effective against gram-positive pathogens. The findings displayed that the antibacterial activity of ZnO NPs is related to the particle size.This new environmentally friendly synthesis approach is a suitable technique for large-scale commercial production and can be considered as an alternative to chemical methods.
Keywords: Zinc oxide nanoparticles; green synthesis; Amaranth; Celosia cristata L.; antibacterial activity; photo catalysis; Basic violet 39; Basic yellow 28; ZINC-OXIDE NANOPARTICLES; LEAF EXTRACT; METAL NANOPARTICLES; MEDIATED SYNTHESIS; PLANT-EXTRACT; BIOSYNTHESIS; DEGRADATION; ANTIOXIDANT; PARAMETERS; INDICA; Chemistry; Engineering